Ultrasound‐Assessed Gastric Antral Area Correlates With Aspirated Tube Feed Volume in Enterally Fed Critically Ill Patients. (16th December 2016) - Sharma, Vibhu; Gudivada, Deepthi; Gueret, Renaud; Bailitz, John
Abstract : Background: Enteral tube feed (ETF) intolerance occurs frequently in hospitalized patients and more so in critically ill patients. Most critical care nurses continue to assess gastric residual volume (GRV), especially among those with a history of ETF intolerance. We hypothesized that ultrasound assessment of GRV correlates directly with aspirated tube feed volume. Methods: This was a prospective cohort study of a convenience sample of critically ill mechanically ventilated patients admitted to an intensive care unit receiving ETF. The gastric antrum was imaged using the aorta and inferior vena cava (IVC) as landmarks concurrently and simultaneously using a curvilinear probe in the midline. All ultrasound measurements were performed at 30 degrees head up, in the supine position, and prior to the assessment of GRV by nursing staff blinding the ultrasonographer to gastric volume aspirated. Gastric antral area was determined by assessing anteroposterior (AP) and craniocaudal (CC) diameters of the gastric antrum. Results: Gastric cross‐sectional area (CSA) using IVC as a landmark ( R 2 = 0.92, P < .0001) and aorta as a landmark ( R 2 = 0.86, P < .0001) correlated with aspirated volume. CC diameter of the stomach measured using the aorta as a landmark correlated with aspirated volume and increased linearly with increasing GRV ( R 2 = 0.78, P < .0001). A CC diameter of <10 cm using the aorta as a landmark predicted a gastric volume of <500 mL. Conclusions: Ultrasound assessment provides accurate assessment of gastric volume in real‐life settings, and the CC diameter of the gastric antrum provides a simple surrogate of GRV.